Mediterranean quarantines, 1750-1914 : space, identity and power - Chircop, John; Martinez, Francisco Javier (Manchester : Manchester University Press, 2018)
Mediterranean quarantines investigates how quarantine, the centuries-old practice of collective defence against epidemics, experienced significant transformations from the eighteenth century in the Mediterranean Sea, its original birthplace. The new epidemics of cholera and the development of bacteriology and hygiene, European colonial expansion, the intensification of commercial interchanges, the technological revolution in maritime and land transportation and the modernisation policies in Islamic countries were among the main factors behind such transformations. The book focuses on case studies on the European and Islamic shores of the Mediterranean showing the multidimensional nature of quarantine, the intimate links that sanitary administrations and institutions had with the territorial organisation of states, international trade, the construction of national, colonial, religious and professional identities of political regimes.
9 Epidemics, quarantine and state control in Portugal, 1750-180510 Quarantine and British 'protection' of the Ionian Islands, 1815-64; 11 Inland sanitary cordons and liberal administration in southern Europe: Mallorca (Balearic Islands), 1820-70; Index.
Includes bibliographical references and index.
English.
JSTOR
Keywords: Quarantine -- Mediterranean Region -- History; Quarantine -- Political aspects -- Mediterranean Region -- History; Quarantine -- Law and legislation -- Mediterranean Region -- History; Quarantine -- history; Mediterranean Region; European history; History of medicine; History; History: earliest times to present day; History: specific events and topics; Humanities; Medicine; Medicine: general issues; Modern history to 20th century: c 1700 to c 1900.; Regional and national history; Social and cultural history; Society and social sciences Society and social sciences; MEDICAL -- Forensic Medicine; MEDICAL -- Preventive Medicine; MEDICAL -- Public Health; MEDICAL / History; Quarantine; Quarantine -- Law and legislation; Mediterranean Region; Identity; Long 19th century; Mediterranean; Power; Quarantine; Space; History